Air Conditioning System Powered by Solar Energy (International Journal of Innovative Research in Engineering & Management, 2021)
Solar-powered air conditioning systems are often extremely  cost-effective when used in residential and commercial  buildings. Today, energy is the greatest issue confronting  humanity. Energy consumption is increasing due to the  growing global population and the developing nations'  economies. Solar energy is therefore the main alternative  energy source that can meet the energy demand. For warm  and humid regions, sustained comfort within the air  conditioner is extremely important. Due to the intensive usage  of the air conditioning system, the energy demand in mid summer increases. In order to overcome this shortfall in CO2  emissions which contributes to global warming, the country  faced an enormous problem in the electricity scarcity, while  the vapor compression air conditioning system disturbs the  stratospheric layer of ozone because of the use of  chlorofluorocarbons (CFCs) in coolants. Solar energy air  cooling may be utilized with absorption chillier with solution  of lithium bromide and water. The solar-powered air  conditioning system helps to reduce the usage of fossil fuel.  Liquid Dry Air Conditioning (LDAC) is one of the most  efficient and environmentally friendly air conditioning  technologies. LDAC may be powered by minimal energy,  such as solar electricity. The usage of Si solar cells with  structured glass packing covers improved conversion  efficiency by 6% at normal angle of incidence.
Keywords: Air Conditioning System; CFC; Fossil Fuels; Photovoltaic; Solar Energy